Development of Natural Mosaic from Moringa Pods for Craft Products: Natural Mosaic from Moringa Pods - chulacupt, supa (Journal of Home Economics Technology and Innovation, 2023)
The objectives of this research were to: study the optimum conditions to soften Moringa pods into natural mosaics, create craft products from natural mosaics, and survey consumer’s satisfaction towards craft products made from natural mosaics of Moringa pods. The research method was designed to study the optimum conditions to soften Moringa pods. Two primary factors were types of conditioners, namely, cationic softener and glycerin and 3 levels of soaking duration which were 1, 3 and 5 days. The factorial in CRD method was applied to the experiments of natural mosaics’ physical properties under 5 categories i.e., tensile strength, moisture, color measurement, gloss and thickness. When the experiment was accomplished, natural mosaics were recreated into artisan products and the assessment of customer satisfaction on the products was collected from 100 respondents. The results revealed that the optimum condition to soften Moringa pods was to soak it in cationic softener for 1 day and that made the tensile strength of Moringa pods reach 4.15 N. The lowest value of moisture was 3.21% and the highest value of brightness (L*) was 79.29%. From the value of the red and green (a*) illuminant, red had the lowest value at 4.01. Apparently, the value of yellow in the yellow and blue (b*) appeared at 31.62. Furthermore, the highest value of color contrast (Delta E) was 9.84 and the lowest value of thickness was 1.89 mm/inch. The highest value of gloss depicts was 2.43. The Natural mosaic prototypes produced. The overall satisfactory score of natural mosaic craft products from Moringa pods was at high level with a mean value of 4.27.